Titania Nanotubes-Bonded Sulfamic Acid as an Efficient Heterogeneous Catalyst for the Synthesis of n-Butyl Levulinate - Zhou, Shuolin; Lei, Min; Bai, Junzhuo; Liu, Xianxiang; Wu, Lu; Long, Min; Huang, Keying; Yin, Dulin (Frontiers in Chemistry, 2022)
The titania nanotubes-bonded sulfamic acid (TNTs-NHSO3H) catalyst was designed and successfully fabricated by the post-synthesis modification method. The as-prepared catalyst was characterized by a variety of characterization techniques, including Fourier transform infrared (FT-IR) spectroscopy, X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray diffraction (XRD) analysis, and thermogravimetry-differential thermal gravimetry (TG-DTG). The crystal structure of the TNTs still maintained during the modification process. Although the BET surface area was decreased, the amount of Brønsted acid sites can be efficiently fabricated on the TNTs. The catalytic activity of TNTs-NHSO3H was examined for the synthesis of n-butyl levulinate (BL) from levulinic acid (LA) and furfuryl alcohol (FA). A relatively high selectivity (99.6%) at 99.3% LA conversion was achieved for esterification of levulinic acid owing to the strong Brønsted acidity sites. And also, the TNTs-NHSO3H catalyst exhibited a higher reactivity for alcoholysis of FA and the yield of BL reached 90.4% with 100% FA conversion was obtained under the mild conditions.